Systems analysis and design people, processes and projects - Siau, Keng; Chiang, Roger H. L.; Hardgrave, Bill C. (Advances in management information systems, 2011)
Focuses on the personal and socio-technical aspects of systems analysis and design. Chapters are grouped into three categories: people and social systems, socio technical processes, and project teams.